Diplomasi Budaya Indonesia dan Rusia dalam Lirik Lagu Rayuan Pulau Kelapa dan Versi Rusia Pesnja Ostrova Pal’m - Widyatmoko, Edelleit Rose; Kaprisma, Hendra (Paradigma: Jurnal Kajian Budaya, 2020)
The focus of this study is the aspects of cultural diplomacy in Pesnja Ostrova Pal’m, Russian version of Rayuan Pulau Kelapa. This song was translated into Russian in 1957 by Vladimir Korchagin as an editor at the Central Studio of Documentary Film, with language formulation according to Russian perspective. As a major theory, this study uses Norman Fairclough’s three-dimension critical discourse analysis theory approach (1997, 2003, and 2013)—text analysis, discursive practice, and social practice. The result of the study shows that the language transfer between Rayuan Pulau Kelapa and Pesnja Ostrova Pal’m was a major contribution to cultural diplomacy between the two countries. Through Rayuan Pulau Kelapa and Pesnja Ostrova Pal’m, a close and sustainable partnership between Indonesia and Russia was formed.